The Roles of LMX, Readiness for Change and Organizational Trust on Employee Behaviours: the Moderating Effects of Organizational Support Constructs - Thompson, Lee (Auckland University of Technology, 2018)
Leader member exchange (LMX) is linked to a number of employee behaviours, although the influence within the context of change is unknown. The present study focuses on those experiencing change at work and tests both readiness for change and organizational trust as mediators of the LMX-work outcome relationships. In addition, Organizational Support Theory suggests that employees may reciprocate with stronger behaviours if they perceive greater support from their organization or identify that their supervisor shares characteristics of the organization. Using data from 393 New Zealand employees and PROCESS analysis with perceived organizational support (POS) and supervisor’s organization embodiment (SOE) as moderators, we find that the LMX–work outcome relationships are mediated by both readiness for change and organizational support. In addition, we find that both SOE and POS moderate the LMX–organizational trust relationship, SOE moderates citizenship behaviour benefiting the organization, while POS moderates counter-productive work behaviour during change. The findings are discussed in terms of their implications for organizational change initiatives. The dissertation fills a gap around understanding of organizational context in relation to change reactions, and it is argued the mediated pathway approach sheds light on the way support perceptions build readiness for change and organizational trust which ultimately impacts upon change recipient work behaviours.
Keywords: Organisational change; Leader-member exchange; Organisational trust; POS; SOE; CPWB; OCB; Turnover intentions; Readiness for change